Polymer electrolyte with ion-selective linear channel and preparation method and application thereof

By covalently grafting the fluoropolymer segment framework and the polymer monomer containing metal cations, polymer electrolytes with ion-selective linear channels were prepared, which solved the problem that existing electrolytes could not have both high strength, low thickness and high cation migration number, and achieved a higher energy density and safer sodium metal battery.

CN119725710AActive Publication Date: 2025-03-28UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411888813.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing single-ion polymer electrolytes cannot have high strength, low thickness and high cation migration numbers, resulting in bottlenecks in sodium metal batteries in terms of high energy density and safety.

Method used

By covalently grafting the fluoropolymer segment framework and the polymer monomer containing metal cations, polymer electrolytes with ion-selective linear channels are prepared to achieve high strength, low thickness and high cation migration number electrolytes.

Benefits of technology

This electrolyte significantly improves energy density and structural stability in sodium metal batteries, reduces the risk of short circuits inside the battery, and improves the cycling stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725710A_ABST
    Figure CN119725710A_ABST
Patent Text Reader

Abstract

The invention provides a polymer electrolyte with an ion-selective linear channel and a preparation method and application thereof, and belongs to the technical field of sodium metal batteries, and the preparation method specifically comprises the following steps: dissolving a fluorine-containing polymer and a sodium-containing cationic polymer monomer into a first organic solvent, stirring to obtain a mixed solution A, adding a metal salt catalyst and an amine catalyst, and stirring to obtain a second organic solvent; after stirring, reacting for 18-24 hours at the temperature of 100-150 DEG C, cooling, precipitating a grafted copolymer by using a second organic solvent, dissolving and precipitating for multiple times, and drying to obtain the polymer electrolyte with the ion selective linear channel. The-SO3Na structure in the obtained polymer electrolyte can realize a transmission channel of single Na < + >, effectively accelerate ion transport and reduce the ion concentration gradient in the electrolyte; and meanwhile, under the condition that an electrolyte film with the thickness of only 10-16 microns is formed, the electrolyte film still has relatively high strength, so that dendritic crystal growth is jointly inhibited, and the stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium metal batteries, and in particular relates to a polymer electrolyte with an ion-selective linear channel and a preparation method and application thereof. Background Art

[0002] As the global demand for efficient energy storage and green energy technology continues to increase, high energy density batteries have become a key goal of the next generation of battery technology. Traditional liquid electrolytes have some bottlenecks in terms of safety, stability and energy density, especially in high power, high voltage and high temperature environments.

[0003] Polymer electrolytes based on traditional polyvinylidene fluoride (PVDF) have attracted widespread attention due to their good electrochemical stability. However, the semi-crystalline state of PVDF causes the polymer to have low ionic conductivity, and severe dehydrogenation (HF) reactions are prone to occur during electrochemical charge and discharge, which will corrode the interfacial lithium metal and solid electrolyte interface (SEI), thereby worsening the interfacial ion deposition environment. At the same time, the sodium salt based on PVDF polymer electrolyte contains both anions and cations, resulting in a low electrolyte cation migration number, and the high thickness of the electrolyte (>65μm) will also cause problems such as increased internal ion concentration gradients and uneven electric fields at the electrode / electrolyte interface, resulting in uneven deposition of interfacial ions, promoting sodium metal dendrite growth and internal short circuits in the battery.

[0004] The gel single-ion polymer quasi-solid electrolyte with ion-selective conduction properties uses a single ion conductor to avoid interference from multiple ions, which can effectively increase the cation migration number, reduce the ion concentration gradient inside the electrolyte, and improve the electric field uniformity of the electrolyte / electrode interface.

[0005] Chinese patent CN 111326788 A discloses a single-ion polymer electrolyte system and its preparation method and application, but the thickness of the electrolyte is still relatively large (50-300 μm). Thick electrolytes will extend the ion path and increase internal impedance. At the same time, high thickness will also increase the proportion of inactive substances in the battery and reduce the battery energy density.

[0006] Chinese patent CN 111100249 A discloses a single-ion polymer electrolyte and its preparation method and lithium-ion battery. Although the method increases the electrolyte cation migration number to alleviate the internal concentration gradient, its electrolyte strength is less than 22Mpa. Low-strength electrolytes are difficult to resist the high stress-strain changes in long battery cycles and are easily pierced by dendrites, causing internal short circuits in the battery.

[0007] Therefore, preparing ion-selective electrolytes that have high strength, low thickness and high cation migration number can promote the development of high-energy-density batteries towards higher energy density and greater safety. Summary of the invention

[0008] In view of the problem that existing single-ion polymer electrolytes cannot have high strength, low thickness and high cation migration number, the present invention provides a polymer electrolyte with ion-selective linear channels and a preparation method and application thereof. By covalently grafting a fluorine-containing polymer segment skeleton with a polymer monomer containing metal cations, a polymer electrolyte with high strength, low thickness and high cation migration number is obtained, which helps to achieve a sodium metal battery with higher energy density.

[0009] In order to achieve the above purpose, the technical method adopted by the present invention is as follows:

[0010] A polymer electrolyte with an ion-selective linear channel, the chemical structure of which is:

[0011]

[0012] Among them, m, n, o are all positive integers, n>1, and m:n:o=100:(9~13):(10~15).

[0013] A method for preparing a polymer electrolyte having an ion-selective linear channel comprises the following steps:

[0014] Step 1, dissolving a fluorine-containing polymer and a sodium-containing cationic polymer monomer in a first organic solvent in a mass ratio of (1-3): (0.5-2), and stirring to obtain a mixed solution A; wherein the mass ratio of the polymer solute to the first organic solvent is (1-3): (10-20);

[0015] Step 2, adding a metal salt catalyst and an amine catalyst in a molar ratio of (350-410): (0.2-1) to the mixed solution A, stirring to obtain a mixed solution B; wherein the mass ratio between the metal salt catalyst and the fluorine-containing polymer is (110-125): (0.5-2);

[0016] Step 3, placing the mixed solution B in nitrogen or a rare gas, reacting at 100-150° C. for 18-24 hours, cooling to room temperature, and precipitating the grafted copolymer using a second organic solvent that is incompatible with the fluorine-containing polymer and the sodium-containing cationic polymer monomer;

[0017] Step 4: The obtained copolymer is dissolved and precipitated for multiple times, and after removing the metal salt catalyst, it is dried to obtain a polymer electrolyte having an ion-selective linear channel.

[0018] Furthermore, the fluorine-containing polymer in step 1 is at least one of polyvinylidene fluoride (PVDF) and poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP).

[0019] Furthermore, the sodium-containing cationic polymer monomer in step 1 is at least one of sodium β-styrene sulfonate, sodium 4-styrene sulfonate, sodium vinyl sulfonate, sodium dodecylbenzene sulfonate, and sodium thiomethane sulfonate.

[0020] Furthermore, the metal salt catalyst in step 2 is a copper salt catalyst.

[0021] Furthermore, the copper salt catalyst includes a monovalent copper salt catalyst and a divalent copper salt catalyst, and the molar ratio of the two is (0.1-1): (3-7).

[0022] Furthermore, the monovalent copper salt catalyst is specifically at least one of cuprous chloride, cuprous bromide, and cuprous iodide, and the divalent copper salt catalyst is specifically at least one of cupric chloride, cupric bromide, and cupric fluoride.

[0023] Furthermore, the amine catalyst in step 2 is specifically at least one of pentamethyldiethylenetriamine, triethylamine, p-phenylenediamine, and ethylenediamine.

[0024] Furthermore, the specific process of washing the precipitate in step 4 is: first dissolving the obtained copolymer in the third organic solvent, and then precipitating it with the second organic solvent, and repeating it 3 to 5 times.

[0025] Furthermore, the first organic solvent and the third organic solvent are at least one of N-methylpyrrolidone, dimethyl sulfoxide, and tetrahydrofuran.

[0026] Furthermore, the second organic solvent is at least one of methanol, anhydrous ethanol and n-hexane.

[0027] Furthermore, in step 4, the drying temperature is 60-80° C. and the drying time is 24-48 hours.

[0028] The invention also proposes application of the obtained polymer electrolyte with ion-selective linear channels in sodium metal batteries.

[0029] A sodium metal battery comprises a positive electrode, a gel polymer electrolyte and a sodium negative electrode, wherein the gel polymer electrolyte is prepared based on the polymer electrolyte having an ion-selective linear channel.

[0030] Furthermore, the specific preparation process of the gel polymer electrolyte is as follows:

[0031] Step A, mixing the polymer electrolyte having an ion-selective linear channel and a fourth organic solvent in a mass ratio of (1-3): (8-12), and dissolving in a water bath to form a viscous and transparent slurry;

[0032] Step B: evenly apply the slurry on the substrate, and after drying, obtain an electrolyte film, which is then immersed in a plasticizer for 12 to 24 hours to form a gel polymer electrolyte.

[0033] Furthermore, the temperature of the water bath dissolution is 60-80°C.

[0034] Furthermore, the thickness of the electrolyte film is 10-16 μm.

[0035] Furthermore, the plasticizer is three of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, and propylene carbonate.

[0036] Furthermore, the fourth organic solvent is at least one of N-methylpyrrolidone, dimethyl sulfoxide, and tetrahydrofuran.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1. The present invention proposes a polymer electrolyte with an ion-selective linear channel and a preparation method and application thereof. By controlling the ratio between the fluorine-containing polymer chain segment skeleton and the sodium-containing cationic polymer monomer, utilizing the synergistic effect of metal salt catalysts and amine catalysts, a covalent bond addition reaction is carried out on the fluorine-containing polymer and the sodium-containing cationic polymer monomer at high temperature to prepare a polymer electrolyte with an ion-selective linear channel;

[0039] 2. The -SO3Na structure in the polymer electrolyte obtained by the present invention can realize a single Na + The transmission channel of the anion grafting and fixing structure eliminates the anion input into the structure, thereby increasing the Na + The migration number effectively accelerates ion transport, reduces the ion concentration gradient in the electrolyte, and thus inhibits dendrite growth;

[0040] 3. When the polymer electrolyte obtained by the present invention is used in a sodium metal battery, it is necessary to first make an electrolyte film and then soak it to form a gel polymer electrolyte; compared with the traditional single-ion polymer electrolyte, the polymer electrolyte obtained by the present invention can ensure that it still has a high strength when forming an electrolyte film with a thickness of only 10 to 16 μm, and the electrolyte film can effectively solve the problem of uneven deposition of interfacial ions caused by factors such as large concentration polarization and uneven electric field at the electrode / electrolyte interface in traditional high-thickness polymer electrolytes, and fundamentally inhibit the growth of interfacial nanometal dendrites, thereby effectively preventing internal short circuits in the battery;

[0041] 4. Preferably, the structure of the polymer electrolyte based on the sodium styrene sulfonate structure contains a rigid non-rotating benzene ring structure (aromatic bond), which has high structural stability and a bond energy of up to 150 kJ / mol, which is much higher than ordinary carbon-carbon single bonds and double bonds, thereby effectively improving the structural stability of the polymer electrolyte based on the sodium styrene sulfonate structure at ultra-thin thickness. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 The polymer electrolyte having ion-selective linear channels obtained in Example 1 1 H spectrum;

[0044] Figure 2 TEM (transmission electron microscope) image of the polymer electrolyte having ion-selective linear channels obtained in Example 1;

[0045] Figure 3 The cycle diagram of the Na||NVP battery assembled with the polymer electrolyte having ion-selective linear channels obtained in Example 1 and the polymer electrolyte obtained in Comparative Example 1;

[0046] Figure 4 The charge-discharge curve of the Na||Na symmetric battery assembled with the polymer electrolyte having ion-selective linear channels obtained in Example 1;

[0047] Figure 5 The Na||Na symmetric battery assembled with the polymer electrolyte having ion-selective linear channels obtained in Example 1 is 0.03-0.3 mA cm -2 Constant current test results at current density of ;

[0048] Figure 6 The constant current test results of the Na||NVP battery assembled with the polymer electrolyte having ion-selective linear channels obtained in Example 1 at a voltage range of 2.8 to 4.8 V and a current density at a rate of 0.4C. DETAILED DESCRIPTION

[0049] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with the examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. All raw materials of the present invention are not particularly limited in their sources, and can be purchased on the market or prepared according to conventional methods well known to those skilled in the art.

[0050] Example 1

[0051] This embodiment prepares a polymer electrolyte with ion-selective linear channels, which specifically includes the following steps:

[0052] Step 1, dissolving poly(vinylidene fluoride-co-hexafluoropropylene) and sodium 4-styrene sulfonate in dimethyl sulfoxide at a mass ratio of 1.73:1, and magnetically stirring to obtain a mixed solution A; wherein the mass ratio of the polymer to the dimethyl sulfoxide is 1:6.98;

[0053] Step 2, adding a monovalent cuprous bromide catalyst, a divalent cupric bromide catalyst and pentamethyldiethylenetriamine in a molar ratio of 286:49:0.9 to the mixed solution A, and stirring to obtain a mixed solution B; wherein the mass ratio between the metal salt catalyst and the poly(vinylidene fluoride-co-hexafluoropropylene) polymer is 115.38:1;

[0054] Step 3, placing the mixed solution B in a three-necked flask filled with nitrogen atmosphere, reacting at 120° C. for 24 hours, cooling to room temperature, and precipitating the grafted copolymer using methanol;

[0055] Step 4: The obtained copolymer is dissolved in dimethyl sulfoxide, and then precipitated with methanol. After repeating the dissolution and precipitation for 4 times, the monovalent copper salt catalyst and the divalent copper salt catalyst are removed, and finally placed in a vacuum oven at 60° C. and dried for 24 hours to remove the solvent in the polymer, thereby obtaining a polymer electrolyte with an ion-selective linear channel.

[0056] The polymer electrolyte with ion-selective linear channels obtained in this example is characterized in terms of physical phase.

[0057] Different coordination environments of H elements in the polymer structure, as well as bond lengths and bond angles of different bonding conditions, will show different position peaks in the H element spectrum of the nuclear magnetic resonance spectrometer (NMR), thereby proving the spatial structure of the grafted polymer. Therefore, the polymer electrolyte with ion-selective linear channels obtained in this example was dissolved in a polar solvent of deuterated dimethyl sulfoxide and placed in an NMR device for testing. 1 H spectrum, the results are as follows Figure 1As shown, there are three different H coordination environments (a, b, c). Specifically, 2.3 and 2.9 PPM in the H spectrum correspond to the H element at position a, and 6.5 and 7.5 PPM correspond to the H elements at positions b and c, respectively, which are consistent with the chemical structure of the polymer electrolyte with ion-selective linear channels obtained in this embodiment.

[0058] The TEM test results of the polymer electrolyte with ion-selective linear channels obtained in this example are as follows: Figure 2 As shown, the obtained polymer electrolyte has a regular lattice structure with a lattice spacing of Since the -SO3Na structure in the obtained polymer electrolyte can realize a single Na + The transmission channel of the anion grafting and fixing structure eliminates the anion input into the structure, thereby increasing the Na + Migration number: In the lattice structure, the linear transmission channel can effectively accelerate ion transport, thereby reducing the ion concentration gradient in the electrolyte and inhibiting dendrite growth.

[0059] The polymer electrolyte with ion-selective linear channels obtained in this example was tested for strength using a universal testing machine. The results are as follows: Figure 3 As shown, since the obtained polymer electrolyte has a rigid segment polystyrene structure, its high bond energy makes its strength as high as 43.3 MPa.

[0060] In order to better illustrate the positive effects of the polymer electrolyte with ion-selective linear channels obtained in this embodiment, a Na||NVP battery and a Na||Na symmetric battery are assembled for illustration.

[0061] When assembling Na||NVP batteries, use a 12mm diameter Na3V2(PO4)3(NVP) film as the positive electrode, a 14mm diameter sodium metal disc as the negative electrode, a 17mm diameter gel polymer electrolyte to separate the positive and negative electrodes, a steel sheet as the current collector, and a spring sheet as a gasket to assemble a 2032 button cell, namely a Na||NVP battery. After the battery is packaged, place it in a 60°C oven for 24 hours to allow the polymer electrolyte to fully contact and infiltrate the positive and negative electrode interfaces.

[0062] Specifically, the preparation process of the positive electrode sheet is as follows:

[0063] The positive electrode material NVP, the conductive additive C45, and the binder polyvinylidene fluoride were mixed in an N-methylpyrrolidone (NMP) solvent in a mass ratio of 8:1:1. The mixture was stirred magnetically at room temperature for 12 h to obtain a uniform positive electrode slurry with uniform components and a positive electrode material mass fraction of 11.1%. The slurry was coated on a carbon-coated aluminum foil. The thickness of the scraper was controlled to 900 μm, and the slurry was evenly coated on an automatic coating machine. The slurry was placed in an oven at 80 °C and vacuum dried for 24 h. After the solvent evaporated, an NVP film was obtained, which was cut into discs with a diameter of 12 mm as the positive electrode sheet. The load was controlled to be 2.2 mg cm -2 .

[0064] Specifically, the preparation process of the gel polymer electrolyte is:

[0065] The polymer electrolyte with ion-selective linear channels obtained in this embodiment is mixed with dimethyl sulfoxide solvent in a mass ratio of 1:12, and placed in a water bath at 60°C to dissolve to form a viscous and transparent slurry; the slurry is evenly coated on a rigid substrate, and evenly coated on an automatic coating machine by controlling the thickness of the scraper to 400μm, and placed in an oven at 60°C, vacuum dried for 24 hours, and after the solvent evaporates, the electrolyte film is dried to obtain a disc with a thickness of 11μm and a diameter of 17mm; the disc is immersed in a plasticizer for 24 hours to form a gel polymer electrolyte. The plasticizer is composed of ethylene carbonate: dimethyl carbonate: fluoroethylene carbonate in a volume ratio of 10:10:1.

[0066] The assembled Na||NVP battery was tested with a constant current density of 0.4C at a voltage range of 2.8 to 4.8 V. The results are as follows: Figure 4 As shown, it still has 100mAh g after 300 cycles. -1 discharge capacity.

[0067] When assembling a Na||Na symmetric battery, the only difference from the process of assembling a Na||NVP battery is that the sodium metal disc is used as the positive electrode; the other structures and assembly processes remain unchanged. The resulting Na||Na symmetric battery has a current density of 0.03-0.3 mA cm -2 The constant current test was carried out at a current density of Figure 5 As shown, it is shown that the Na||Na symmetric battery based on the polymer electrolyte with ion-selective linear channels obtained in this embodiment can withstand a large test current density and has excellent cycle stability.

[0068] Through the Na||Na symmetric battery test, the conductivity of the gel polymer electrolyte obtained in this embodiment at 60°C is higher than 10 -5 S cm -1 , cation migration number>0.9.

[0069] Comparative Example 1

[0070] This comparative example prepares a dual-ion polymer electrolyte, which specifically includes the following steps:

[0071] Step 1, dissolving poly(vinylidene fluoride-co-hexafluoropropylene) and sodium bistrifluoromethanesulfonyl imide (i.e., sodium salt containing cation and cation dual ions) in N-methylpyrrolidone at a mass ratio of 1.25:1, and magnetically stirring to obtain a mixed solution A; wherein the mass ratio of poly(vinylidene fluoride-co-hexafluoropropylene) to N-methylpyrrolidone is 1:10;

[0072] Step 2, stirring the mixed solution A to a uniform transparent solution, and then coating the slurry on a rigid substrate, by controlling the thickness of the scraper to 800 μm, and coating evenly on an automatic coating machine;

[0073] Step 3: Place the coated film in an oven at 60°C and vacuum dry it for 24 hours. After the solvent evaporates, dry it to obtain a dual-ion polymer electrolyte. Use a cutter to cut the dual-ion polymer electrolyte into 100 μm thick and 17 mm diameter discs, and immerse them in a plasticizer composed of ethylene carbonate: dimethyl carbonate: fluoroethylene carbonate in a volume ratio of 10:10:1 to obtain a gel polymer electrolyte for battery installation.

[0074] The strength of the dual ion polymer electrolyte obtained in this comparative example was tested using a universal testing machine. The results are as follows: Figure 3 As shown, it can be seen that its strength is only 5.5 MPa, which is much lower than the 43.3 MPa strength of the polymer electrolyte (single cation) with ion-selective linear channels obtained in Example 1. The high strength characteristics of the polymer electrolyte can effectively improve the stability of the battery during long cycles.

[0075] The Na||NVP battery and the Na||Na symmetric battery were assembled respectively according to the method of Example 1.

[0076] For Na||NVP battery, constant current test was performed at a current density of 0.4C rate in the voltage range of 2.8~4.8V. The results are as follows Figure 4 As shown, it can be seen that the battery performance has obviously decayed after 60 cycles.

[0077] Through the Na||Na symmetric battery test, the cation migration number of the gel polymer electrolyte obtained in this comparative example at a temperature of 60° C. is 0.31, which is much lower than that of the gel polymer electrolyte obtained in Example 1.

[0078] Example 2

[0079] In this embodiment, a polymer electrolyte with an ion-selective linear channel is prepared. The process is different from that in Example 1, except that the ratio of poly(vinylidene fluoride-co-hexafluoropropylene) and sodium 4-styrenesulfonate in step 1 is adjusted to 1:1, and the mass ratio of the polymer to dimethyl sulfoxide is adjusted to 2:11; the other steps remain unchanged.

[0080] Compared with Example 1, this example increases the proportion of rigid chain sodium styrene sulfonate in the polymer electrolyte. Its low rotation and high glass transition temperature characteristics reduce the segment mobility of the polymer electrolyte, thereby weakening its ion transport capacity. By assembling Na||NVP batteries, constant current tests were performed at a current density of 0.4C at a voltage range of 2.8 to 4.8 V. The results are as follows: Figure 6 As shown, it can be seen that it only has 75mAh g -1 The discharge capacity of the battery is very good, but its cycle stability is still very good, and it can be cycled for at least 400 times without attenuation.

[0081] The present invention uses specific examples to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enables any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A polymer electrolyte having an ion-selective linear channel, characterized in that: Its chemical structure is: Among them, m, n, o are all positive integers, n>1, and m:n:o=100:(9~13):(10~15).

2. A method for preparing a polymer electrolyte having an ion-selective linear channel, characterized in that: The following steps are involved: Step 1, dissolving a fluorine-containing polymer and a sodium-containing cationic polymer monomer in a first organic solvent in a mass ratio of (1-3): (0.5-2), and stirring to obtain a mixed solution A; wherein the mass ratio of the polymer solute to the first organic solvent is (1-3): (10-20); Step 2, adding a metal salt catalyst and an amine catalyst in a molar ratio of (350-410): (0.2-1) to the mixed solution A, stirring to obtain a mixed solution B; wherein the mass ratio between the metal salt catalyst and the fluorine-containing polymer is (110-125): (0.5-2); Step 3, placing the mixed solution B in nitrogen or a rare gas, reacting at 100-150° C. for 18-24 hours, cooling to room temperature, and precipitating the grafted copolymer using a second organic solvent that is incompatible with the fluorine-containing polymer and the sodium-containing cationic polymer monomer; Step 4: The obtained copolymer is dissolved and precipitated multiple times, and after removing the metal salt catalyst, it is dried to obtain the polymer electrolyte having ion-selective linear channels as claimed in claim 1.

3. The method for preparing a polymer electrolyte having an ion-selective linear channel according to claim 2, characterized in that: The fluorine-containing polymer in step 1 is at least one of polyvinylidene fluoride and poly(vinylidene fluoride-co-hexafluoropropylene).

4. The method for preparing a polymer electrolyte having an ion-selective linear channel according to claim 2, characterized in that: The sodium-containing cationic polymer monomer in step 1 is at least one of sodium β-styrene sulfonate, sodium 4-styrene sulfonate, sodium vinyl sulfonate, sodium dodecylbenzene sulfonate, and sodium thiomethane sulfonate.

5. The method for preparing a polymer electrolyte having an ion-selective linear channel according to claim 2, characterized in that: The metal salt catalyst in step 2 is a copper salt catalyst, including a monovalent copper salt catalyst and a divalent copper salt catalyst, and the molar ratio of the two is (0.1-1): (3-7).

6. The method for surface modification of a polyarylether-based current collector according to claim 5, characterized in that: The monovalent copper salt catalyst is specifically at least one of cuprous chloride, cuprous bromide, and cuprous iodide, and the divalent copper salt catalyst is specifically at least one of cupric chloride, cupric bromide, and cupric fluoride.

7. The method for preparing a polymer electrolyte having an ion-selective linear channel according to claim 2, characterized in that: The amine catalyst in step 2 is specifically at least one of pentamethyldiethylenetriamine, triethylamine, p-phenylenediamine, and ethylenediamine.

8. The method for preparing a polymer electrolyte having an ion-selective linear channel according to claim 2, characterized in that: The specific process of washing the precipitate in step 4 is: first dissolving the obtained copolymer in a third organic solvent, and then using a second organic solvent for precipitation, and repeating 3 to 5 times; the first organic solvent and the third organic solvent are at least one of N-methylpyrrolidone, dimethyl sulfoxide, and tetrahydrofuran; the second organic solvent is at least one of methanol, anhydrous ethanol, and n-hexane.

9. Use of the polymer electrolyte having ion-selective linear channels obtained according to the preparation method according to any one of claims 2 to 8 in sodium metal batteries.

10. A sodium metal battery, characterized in that: The invention comprises a positive electrode, a gel polymer electrolyte and a sodium negative electrode, wherein the gel polymer electrolyte is prepared based on a polymer electrolyte having an ion-selective linear channel obtained by the preparation method according to any one of claims 2 to 8; the specific preparation process of the gel polymer electrolyte is as follows: Step A, mixing the polymer electrolyte having an ion-selective linear channel and a fourth organic solvent in a mass ratio of (1-3): (8-12), and dissolving in a water bath to form a viscous and transparent slurry; Step B: evenly apply the slurry on the substrate, and after drying, obtain an electrolyte film, which is then immersed in a plasticizer for 12 to 24 hours to form a gel polymer electrolyte.

Citation Information

Patent Citations

  • Gel electrolyte based on porous matrix and resisting electrolyte leakage and preparation method thereof

    CN103265721A

  • Gel polymer electrolyte and secondary battery comprising the same

    CN106257732A

  • Fluorine-containing single-ion conductor polymer electrolyte and preparation method and application thereof

    CN106887622A

  • Novel single ion polymer electrolyte and preparation method and application thereof

    CN108091930A

  • Lithium battery single ion conductor polymer electrolyte and preparation method thereof

    CN117913456A